Role and Challenges of Information Technology Increasing Business Competitiveness of Siger Tower Reviewed Aspects of Business Economics on E-Business and E-Commerce - Raden Arum Setia Priadi; Meizano Ardhi Muhammad; Gita Paramita Djausal (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Objektives: Siger Tower Monument, a place where travelers travel, is on the limestone of Bakauheni Village. Related to that, Siger Tower Manager needs to build electronic commerce facility for international marketing of Lampung commodity. Methods / Statistical Analysis: After studying the details of existing commodity snippets only handicraft, selfie booth, rest area with Sumatera zero km point that can be facilitated it also requires preparation and arrangement of electronic business with priority on coffee commodities and derivatives in all stake holders. Test samples in the form of questioners to determine the preparedness of technology stakeholders, controlling the approach used compare the results obtained. Findings: UPTD Siger Tower needs preparation to welcome the opening of JTTS in the midst of land constraints where the tower positions belong to PT ASDP while the tower building belongs to the Lampung Provincial Government. This finding locks the development of management so that there is no form of cooperation that mentions the rights and obligations of the parties. It can be said that the minimum allocation of APBD for the care and development of Tower Siger. Its existence has a crucial position for the image of Lampung because: 1) Located at the point of 0 km Sumatra, near the Port of Bakauheni; 2) Siger Tower Tower landmark of Lampung; 3) Illustration Tower Siger used the community of Lampung as a symbol of Lampung. Phillip Kotler's marketing mix consists of four things that need to be considered to support marketing to answer consumer demand: product, price, place, and promotion, to consider the development of Siger Tower as a tourist destination and icon of Lampung. Local products come from the region's main commodities, coffee (mostly highland robusta) sold in the form of seeds, powder in various brands because of the variety of producers. The arrangement of the electronic business cultivates collaborative development opportunities to build the image of the Siger Tower for coffee connoisseurs, partly from outside Lampung Province. Application / Improvements: Portal providers of tourism support services with marketing information Tower of Siger related to various products to potential development opportunities for major coffee commodities. For the traveler in his rest area, presented the sale of seeds, coffee powder. Keywords: E-Business, E-Commerce, Tower Siger, and Coffee.